Cardiac Magnetic Resonance Imaging in the Diagnosis of Anterolateral Left Ventricular Ballooning, a Variant of Classic Takotsubo Cardiomyopathy. (26th November 2012) - Zbinden, R.; Mutter, M.; Weishaupt, D.
Abstract : Transient left ventricular apical ballooning syndrome is characterized by transient akinesis of the left ventricular apex with basal wall hyperkinesis; this is also known as Takotsubo cardiomyopathy. There are three distinct contractile LV patterns described in the literature: apical, midventricular, and basal ballooning. The apical ballooning pattern is the most frequent pattern. We describe the case of a transient anterolateral left ventricular ballooning fulfilling the definition of Takotsubo cardiomyopathy except for the contractile LV pattern. The diagnosis was supported by cardiac magnetic resonance imaging and by the fact that the anterolateral ballooning resolved completely after 6 weeks.